Соль: [повесть] / Александра Зайцева - Зайцева Александра (Встречное движение, 2022)
Экземпляры: ф. 15 (20240408) / Инвентарный номер: 67637 / Цена: 50.00 / Авт.знак: З-17 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6